ANALISIS FAKTOR RISIKO PADA PENYAKIT KARSINOMA PARU (C34) PASIEN RAWAT INAP DI RUMAH SAKIT BALADHIKA HUSADA JEMBER - Salma Firyal Nabila; Dony Setiawan Hendyca Putra; Sustin Farlinda; Efri Tri Ardianto (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
Lung carcinoma or commonly known as lung cancer is one of the main causes of death from disease in theworld that reach 7.6 million deaths or about 13% of all cancer diagnoses. Baladhika Husada Jember Hospitalis a third-level hospital in Jember Regency that has oncology and chemotherapy services including a cancerdiagnosis. Based on existing data of the morbidity and mortality rates of pulmonary carcinoma are alwaysincreasing from 2016 until 2018. This study aims to analyze the risk factors for lung carcinoma such as age,gender, smoking history, genetic history, and predisposition of other lung disease based on medical records ofinpatients with the pulmonary disorder at Baladhika Husada Hospital in Jember. The research method usedquantitative analysis with a cross-sectional research design. The number of samples was 98 respondents.Data analysis used the chi-square test for bivariate and the logistic regression test for multivariate. Thebivariate analysis result shows that each independent variable had an influence on lung carcinoma cases.Multivariate analysis shows that the variable had a simultaneous influence (p value=0,000). Partially, eachvariable has an influence, age (p value=0,003), smoking history (p value=0,003), genetic history (pvalue=0,002), predisposition of other lung disease (p value=0,000), except on genders (p value=0,857). Theconclusion is the risk factors can explain the effect on the incidence of pulmonary carcinoma by 84.8%. Thisresearch is expected to be used as information to cope with the increased morbidity and mortality rates ofpulmonary carcinoma.